Time-gated confocal microscopy reveals accumulation of exocyst subunits at the plant-pathogen interface - Overdijk, Elysa J R (Journal of experimental botany, 2020)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.